Effects of training with eccentric loads on the performance of futsal players - Sánchez-Sánchez, J.; Guillen Rodríguez, J.; Martín García, D.; Romo Martín, D.; Barrueco García, J.; Bores Cerezal, A.J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of the study was to analyze the effects of a specific 8 week training program that includes eccentric strengthening exercises with isoinertial machines on the physical fitness of semi-professional futsal players. The 10 players (23.73±5.5 years; 69.91±8.47 kg; 172.27±6.62 cm) were randomly divided into two groups: Group body weight (GAUT; n = 5) and Group Machines (GMAQ, n = 5). Both groups conducted an eccentric loading training session per week for 8 competition microcycles. The player was evaluated before (pre-test), at the end (post-test) and 2 weeks after (re-test) the training program. The tests used were: sit-and-reach test; "squat jump" test (SJ) and “countermovement jump" (CMJ); linear velocity 30 m test with change of direction. The analysis through the Wilcoxon test statistic showed significant improvements in CMJ GAUT (p ≤ 0.05), the linear velocity and the change of direction test in GAUT (p≤0.05) and GMAQ (p≤0.01) speed, but no intergroup differences have been found in any of the variables studied. The results indicate that the eccentric loading exercises may be an effective complement to the specific training programs for futsal players due to its positive impact on important performance variables such as non linear speed.